Cross-organizational communities of practice in design studies : enhancing creativity, collaboration and pre-professional identities in higher education - Mavri, Aekaterini (Cyprus University of Technology, 2020)
The purpose of this work is to investigate the role and impact of cross-organizational (industry-academia) Communities of Practice (CoPs) on learning in Higher Education (HE) Design studies. CoPs are groups of people who share a common interest in an area of ‘endeavor’ and connect to co-create knowledge through practice. This dissertation is motivated by the current gap between academia and industry, regarding the actual – versus the anticipated – knowledge, skills (communication, collaboration, creativity) and personae (vocational relevance) of graduates who transition into the digital creative industries today. This originates from the graduates’ lack of authentic experiences with real-life practice, as well as from the universities’ limitation to keep up with the fast-paced industry developments. This research proposes that robust academia-industry collaborations can enhance academic programs towards bridging this gap. It demonstrates the effective convergence of creativity, collaboration, and authenticity in education through cross-organizational CoPs, by bringing together academic and industrial stakeholders in a technology-supported and curriculum-integrated practice. Following a mixed-methods approach, it captures a diverse body of data to understand and explain the designed and emergent learning phenomena. Findings denote solid member participation levels, made evident in the abundant online and offline CoP exchanges. They also infer significantly higher epistemic and creative outcomes for CoP-participating - versus non-participating - students. The substantial shift in learner perspectives and perceptions of achievement signifies an identity transformation, from the academic toward the pre-professional and professional statuses, induced by the broader membership and context of the CoP. This work empirically demonstrates and validates the critical interlocking of the technological, epistemic and social designs that constitute an appropriate learning ecology for the complex practices of cross-organizational CoPs in HE Design studies. It also provides a structured set of actionable guidelines to assist researchers and practitioners in the adoption of the cross-organizational CoP model, in an aim to enhance learning in the Design disciplines.
Keywords: Communities of practice; Situated learning; Creativity; Vocational relevance; Academia-industry collaboration